Investigating the Impact of Corporate Governance Characteristics on Earnings Management in Chinese Growth Enterprise Market (GEM) Listed Companies - Wu, Yuanxin (2020)
Recently, a lot of studies show that there exist earnings management problems in Chinese listed companies, and the main reason for this is the defects of the governance structure. Therefore, this dissertation studies the effect of corporate governance characteristics on earnings management in Chinese GEM companies. The research sample includes 739 companies from 2010 to 2019, and the Modified Jones model is chosen to measure earnings management. Besides, an in-depth investigation that divides the sample into three industries is adopted. From the results, audit quality, top 10 shareholders’ shareholding, and gender diversity verify the previous hypotheses, while the amount of free cash flow rejects the hypothesis and shows a negative result. And most of the study variables showed the same outcomes among different industries. Therefore, improving the corporate governance mechanism is helpful to fundamentally solve the earnings management problems of listed companies on the GEM and create a more healthy and stable Chinese capital market.